Literatura surda: elementos estéticos presentes nos haicais em Libras - Souza, Abraão Calebe Torres de (Brasil, 2024)
This research aims to show the aesthetic elements present in haiku produced by deaf authors. According to Sutton-Spence; Machado (2023), the haiku textual genre is intended to be a more objective and simple poem for the reader, and we will detect and analyze its aesthetic elements in Deaf Literature. The author Sutton-Spence (2021) mentions that the haiku is a very short poem, between five and fifteen seconds, which is why it is important to detail this genre. Kaneko (2008) gives the best details of the signaled haiku, showing its main characteristics. The trajectory of the written haiku until its arrival in Brazil is covered by Nishikido (2019) who reports that the haiku is traditional Japanese poetry, and consists of the structure of three short verses, which generally relate to nature and highlight beauty or a moment of reflection. The methodology used in this research was bibliographical and qualitative, in which videos produced by deaf authors were collected and detailed in terms of their aesthetic elements, for example, whether there is space and symmetry, classifier, speed and so on. Finally, three videos produced by deaf authors were selected to show the aesthetic elements present in the haiku in Libras. After analysis, several aesthetic elements were evidenced in the production of haiku in Libras.